Transitional Cell Carcinoma and Pseudocirrhosis- A Case Report and Review of the Literature - Gilad Borisovsky; Daniel A. Goldstein; Noa Eliakim-Raz; Shlomit R. Tamir (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Pseudocirrhosis is the occurrence of capsular retraction in patients with metastatic liver disease, usually of breast origin. It usually appears in these patients following chemotherapy and may result from shrinkage of the tumor, with scarring and nodular regeneration. In this article, we describe the first case of pseudocirrhosis, following treatment of transitional cell carcinoma metastatic to the liver. Portal vein thrombosis, a rare complication in pseudocirrhosis, was also detected in this patient.